EFEKTIVITAS MODEL PEMBELAJARAN NUMBER HEAD TOGETHER DENGAN PENDEKATAN OPEN ENDED TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATERI BILANGAN BERPANGKAT KELAS X - Arie Widyastuti; Iswahyudi Joko Suprayitno; Abdul Aziz (Universitas Muhammadiyah Semarang, 2017)
The problems that exist in this research is that students can not understand the concept of rank numbers, the formulas to solve the problems on the operation of rank numbers. In addition, student motivation and discipline in learning is low. This study aims to determine the effectiveness of the learning model of Number Head Together with Open Ended approach to the ability to understand the concept of class X grade matter. This research is an experimental research using technique of sampling technique of Purposive Sampling. The sample in this research is X TB 1 (Experiment) and X TB 2 (Control), the test used is the test of completeness, influence test and average difference test. The result of this research shows that: (1) Student using model Head Head Together reaches 80% classical completeness, (2) motivation and discipline influence to concept comprehension ability 92,10%, (3) difference of mean value ability understanding of experimental class concept 87,68 is better than control class equal to 72,70. So it can be concluded that the learning by using Model Head Head Together with Open Ended approach to the ability of conceptual understanding of effective effective number material. Keywords: Number Head Together, Open Ended, Ability to Understand Concepts.